The Characteristics of Instructional Systematic Design English Online Teaching Environment - Rizky Eka Prasetya (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
The English online learning instructional model became contingent upon organised and guided learning practices by competent English lecturers as instructors in the online situation. There are a few concepts applied to the English instructional online pedagogy for Higher Education and Universities. The purposes of the examinations are to classify the relevance of online instructional learning to conform to English learning and present current or unexpected instructional design into the English online environment. The study employed a convergent parallel design method. This method of choice had depth-analysing and performing parallel analyses, which are considered alternative evidence for discussing the components of the online instructional model. The examination consisted of 52 English lecturers from various Higher Education and Universities. The survey questionnaires were addressed to participants, and interview strategies were identified to collect a distinctive angle and dept-involvement on the English online instructional. Findings of the study have revealed that English lecturers considered learner-centered intended course as very important for their teaching concept while emphasising real-world performance as important for the online environment material. Collaborative approach and concentrate on reliably and validly assessed outcomes become the second phase importance in the online instructional model. Interview protocols thematic analysis exposed that English lecturers should support and organise their particular English online instructional online environment. The general characterised adapted to engage in English online instructional online-based. The condition is because of English lecturers empathising with the appropriate material, approach to the learners’ flexibility, and individual accomplishment in every topic.